Adverse effects as a consequence of being the subject of orthopaedic manual therapy training, a worldwide retrospective survey. (June 2017) - Thoomes-de Graaf, M.; Thoomes, E.J.; Carlesso, L.; Kerry, R.; Rushton, A.
Abstract: Background: Physical therapists (PTs) use a range of manual therapy techniques developed to an advanced level through postgraduate orthopaedic manipulative physical therapy (OMPT) programmes. The aim of this study was to describe the adverse effects experienced by students after having techniques performed on them as part of their OMPT training. Design: A descriptive online survey of current students and recent graduates (≤5 years)m of OMPT programmes across the 22 Member Organisations of the International Federation of Orthopaedic Manipulative Physical Therapists. Results: The questionnaire was completed by 1640 respondents across 22 countries (1263 graduates, 377 students. Some 60% of respondents reported never having experienced adverse effects during their manual therapy training. Of the 40% who did, 66.4% reported neck pain, 50.9% headache and 32% low back pain. Most reports of neck pain started after a manipulation and/or mobilisation, of which 53.4% lasted ≤24 h, 38.1% > 24 h but <3 months and 13.7% still experienced neck pain to date. A small percentage of respondents (3.3%) reported knowing of a fellow student experiencing a major adverse effect. Conclusion: Mild to moderate adverse effects after practising manual therapy techniques are commonly reported, but usually resolve within 24 h. However, this survey has identified the reported occurrence of major adverse effects that warrant further investigation. Highlights: Transient minor to moderate adverse effects to OMPT procedures are common. Out of 1560 respondents, 21.6% report still experiencing adverse effects. A correlation between a history of pre-existing pain and adverse effects was found. Recall bias could have lead to an under-reporting of adverse effects. A screening tool should be validated for use in educational and clinical settings.